Case Report: IVIG causing bilateral papilledema and increased intracranial hypertension in patients with anti-TIF-1γ antibody-positive JDM - Baluta, Sarah; Stojkic, Ivana; Driest, Kyla; Schutt, Christina (Frontiers in Pediatrics, 2024)
Juvenile dermatomyositis is a systemic autoimmune disease characterized by progressive proximal muscle weakness, pathognomonic rashes, and often the presence of myositis-specific antibodies. Consensus treatment plans for pediatric patients with juvenile dermatomyositis recommend steroids and methotrexate as initial therapy. Patients with anti-transcription intermediary factor 1 gamma (anti-TIF-1γ) antibodies tend to have more refractory disease requiring more aggressive treatment with intravenous immunoglobulin, which is typically well tolerated. We describe two pediatric patients diagnosed with anti-TIF-1γ antibody-positive juvenile dermatomyositis who developed persistent increased intracranial pressure following intravenous immunoglobulin treatment. These cases suggest a potential association between treatment with intravenous immunoglobulin and increased intracranial pressure, a side effect that is not readily known. The shared anti-TIF-1γ positivity in both patients may suggest a possible concern for intracranial hypertension among juvenile dermatomyositis patients with this myositis-specific antibody.